Psychological сomponents of miscarriage. Ways to overcome - A. A. Zhyvetska-Denysova; V. B. Tkachenko; I. I. Vorobiova (Zaporožskij Medicinskij Žurnal)
Habitual miscarriage is a stressful condition and a significant factor of frustration for married couples. The psycho-emotional state of the pregnant woman affects the course of the subsequent pregnancy and its outcome. Correction of the psychological component of habitual miscarriage is a promising direction for preventing reproductive losses.